(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The composition of phenolic compounds from samples of the above-ground mass collected during the flowering period and the lines of transformed roots of Artemisia annua L. was analyzed. The efficiency of bioactive compounds extraction using ultrasonic and microwave treatment at different duration and temperature of the process was evaluated. The chemical composition, in particular, the content of caffeylquinic acids and their derivatives as the main active substances in the extracts of wormwood were determined by liquid chromatography with mass-selective and diode-array detectors.